Benchmarking of the English Language Component of the Mature Students’ Entrance Examinations in Ghana against the WASSCE English Language Component - Asafo-Adjei, Ramos (Mediterranean Journal of Social Sciences, 2021)
This paper was purposed on benchmarking the English language component of the Mature Students’ Entrance Examinations (MSEE) (administered in Ghana by universities to select undergraduate candidates) to the English language component of the West African Senior School Certificate Examination (WASSCE) which constitutes the mainstream Ghanaian university undergraduate entrance examination. The qualitative design (specifically, multiple case study design) was employed for this study. Using the multi-stage sampling technique, six Ghanaian universities (from whom eighteen English language component of the MSEE past questions were elicited) and three sets of the WASSCE English language component past questions administered in 2016, 2017 and 2018) were used for the study. O’Leary’s (2014) eight steps of conducting document analysis were used to analyse the data. The study revealed that there are major mismatches between the two sets of examinations in the areas of the test types, the basic language skills tested and the competences tested. The study advanced, to policy makers, suggestions such as testing Speaking and Listening for the improvement of the two sets of examinations.   Received: 11 May 2021 / Accepted: 14 June 2021 / Published: 8 July 2021